Case report: Aplasia cutis congenita of the scalp with bone defect and an exposed sagittal sinus in a trisomy 13 newborn - AlMatrafi, Faisal Rashed; Al-Shammari, Ahmad Ayed; Al Nefily, Raed Mohamed; AlAnazi, Rawan Abdulrahman; Abdulwahab, Abdulrahman Hamed; Ammar, Ahmed Sabry (Frontiers in Pediatrics, 2023)
Aplasia cutis congenita (ACC) is a heterogeneous disorders group with a rare reported incident of 0.5 to 1 in 10,000 births. ACC can be associated with physical defects or syndrome that may help in diagnosis, prognosis and further evaluation of the patient. Trisomy 13 is one of the most common fetal life limiting diagnosis which is associated with ACC of membranous type scalp. The patient was born at 35 weeks of gestation via cesarean sections due to fetal distress. Upon admission to our hospital, her pertinent physical examination revealed a newborn girl with dysmorphic facial features including widely separated eyes, downward slanting of the palpebral fissure, microphthalmia, retrognathia, and low seat ears. She had area of loss of scalp skin and skull bone with seen brain tissue and sagittal sinus were exposed that was measure 6 by 5 cm in size. Additionally, she had a clenched fist and overlapping fingers and rocker bottom feet. Precordium auscultation revealed medium pitched high grade continuous murmur heard best at the pulmonary position with a harsh machinelike quality that often radiated to the left clavicle. Laboratory investigations include basic labs and the TORCH screen was negative. On the 9th day of life, a chromosomal analysis showed a female karyotype with three copies of chromosome number 13 (Trisomy 13) in all 20 metaphase cells counts. The patient was managed with moist gauze dressing, topical antibiotics ointment, and povidone-iodine. However, a multidisciplinary team agreed on do not resuscitate (DNR) with no further surgical intervention as survival rate of trisomy 13 is poor. In this article, we report cases of aplasia cutis congenita of the scalp with dura and bone defect and exposed sagittal sinus in newborn diagnosed to have trisomy 13. It emphasizes the importance of ACC associated syndrome which is having high mortality prior to surgical intervention.